2008
DOI: 10.1097/ajp.0b013e318157233b
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Over Somatosensory Cortex Decreases ExperimentallyInduced Acute Pain Perception

Abstract: Our study highlights the antinociceptive effect of this technique and may contribute to the understanding of the mechanisms underlying pain relief. The pharmacologic prolongation of the excitability-diminishing after-effects would render the method applicable to different patient populations with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 58 publications
7
93
3
6
Order By: Relevance
“…In stroke patients, tDCS enhances aphasia or motor function of the upper and lower extremities (Hesse et al 2007;Monti et al 2008). It also improves the perception of pain (Antal et al 2008) and various symptoms related to chronic pain syndrome (Fregni et al 2006a, b).…”
Section: Discussionmentioning
confidence: 99%
“…In stroke patients, tDCS enhances aphasia or motor function of the upper and lower extremities (Hesse et al 2007;Monti et al 2008). It also improves the perception of pain (Antal et al 2008) and various symptoms related to chronic pain syndrome (Fregni et al 2006a, b).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the simple, safe, and cost-effective brain stimulation methods that have clinical uses 1,27) . Research on invasive and noninvasive nerve stimulation in relation to excitability control of the cerebral cortex is important; research into such kinds of nerve stimulation has investigated them as tools to influence kinesthetic sense perception, functional exercise, and rehabilitation, and generally, to change brain activation potential 8,28) .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, much fewer tDCS studies found significant results with cathodal stimulation. These include improved naming in stroke patients with chronic nonfluent aphasia (Monti et al, 2008), improved motor function in patients with stroke (Boggio, Nunes, et al, 2007;Fregni, Boggio, Mansur, et al, 2005), diminished pain perception in healthy volunteers (Antal, Brepohl, et al, 2008), decreased craving for alcohol (Boggio, Rigonatti, et al, 2008) and foods (Fregni, Orsati, et al, 2008), suppressed motor excitability in control subjects, but no effects in patients with focal dystonia (Lang, Nitsche, Paulus, Rothwell, & Lemon, 2004;Nitsche & Paulus, 2000;Quartarone et al, 2005).…”
Section: Experimental Methodology Of Tdcsmentioning
confidence: 99%
“…Effects of tDCS in humans include changes in behavioral measures, like in motor performance (Vines, Cerruti & Schlaug, 2008;Vines, Nair, & Schlaug, 2006) and cognitive performance 338 E. ANGELAKIS AND E. LIOUTA Floel, Rosser, Michka, Knecht, & Breitenstein, 2008;Fregni, Boggio, Nitsche, 2005;Iyer et al, 2005;Kincses, Antal, Nitsche, Bártfai, & Paulus, 2004;Monti et al, 2008), and in sensory perception (Antal, Nitsche, & Paulus, 2001); changes in electrophysiological measures, such as motor-evoked potentials (MEPs; Ardolino et al, 2005;Furubayashi et al, 2008;Nitsche & Paulus, 2000;Quartarone et al, 2004) or event-related potentials (Keeser et al, 2011;NakamuraPalacios et al, 2011), intramuscular coherence (Power et al, 2006), EEG visual-evoked potentials or pain-evoked potentials (Accornero, Li Voti, La Riccia, & Gregori, 2007;Antal, Brepohl, et al, 2008;Terney et al, 2008), and EEG amplitude (Ardolino et al, 2005;Marshall, Moelle, Hallschmid, & Born, 2004), as well as in brain hemodynamic changes measured by functional magnetic resonance imaging (Baudewig, Nitsche, Raulus, & Frahm, 2001;Kwon et al, 2008;Zheng, Alsop, & Schlaug, 2011), or by positron emission tomography (PET; Lang et al, 2005). Using functional magnetic resonance imaging, Baudewig and colleagues (2001) found decreased regional cerebral blood flow (rCBF) after 5 min of cathodal tDCS at the primary motor cortex, and no changes after anodal tDCS.…”
Section: Primary Effects Of Tdcsmentioning
confidence: 99%